2020
DOI: 10.12680/balneo.2020.307
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pulmonary rehabilitation in improving quality of life in patients with different COPD stages

Abstract: Introduction. Anxiety and depression are frequently associated conditions in COPD patients, and have also significant impact on their quality of life (QoL) and on the course of the disease. Pulmonary rehabilitation (PR) is an adjuvant, non-pharmacological method used in symptomatic COPD patients. The study aimed to evaluate the impact of COPD on QoL depending on disease severity, and to assess the supposedly positive effects of a pulmonary rehabilitation program (PRP) for COPD patients. Material and method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Early initiation of PR can potentially minimize the effect of acute exacerbations on the skeletal muscle and prevent the deterioration of skeletal muscle to a significant extent [23], thus appearing to be an effective strategy to change the course of the disease [24]. Several other studies have demonstrated significant improvement in muscle function and quality of life [25][26][27][28][29][30], psychosocial wellbeing [31], reduction in mortality, and rate of hospitalization [32] following successful completion of PR. The benefits of PR can be further maximized by introducing supplemental nutrition [33,34].…”
Section: Pulmonary Rehabilitation: the Pressing Priority In The Management Of Copdmentioning
confidence: 99%
“…Early initiation of PR can potentially minimize the effect of acute exacerbations on the skeletal muscle and prevent the deterioration of skeletal muscle to a significant extent [23], thus appearing to be an effective strategy to change the course of the disease [24]. Several other studies have demonstrated significant improvement in muscle function and quality of life [25][26][27][28][29][30], psychosocial wellbeing [31], reduction in mortality, and rate of hospitalization [32] following successful completion of PR. The benefits of PR can be further maximized by introducing supplemental nutrition [33,34].…”
Section: Pulmonary Rehabilitation: the Pressing Priority In The Management Of Copdmentioning
confidence: 99%